2017
DOI: 10.1371/journal.pone.0181714
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-HspX antibodies and HspX protein in patient sera for the identification of recent latent infection by Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis is a pathogen causing tuberculosis (TB) a spectrum of disease including acute and asymptomatic latent stages. Identifying and treating latently-infected patients constitutes one of the most important impediments to TB control efforts. Those individuals can remain undiagnosed for decades serving as potential reservoirs for disease reactivation. Tests for the accurate diagnosis of latent infection currently are unavailable. HspX protein (α-crystallin), encoded by Rv2031c gene, is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…We encountered a similar phenomenon in this study, which resulted in 'negative' (< 0) ΔOD values for anti-Acr IgM antibodies. This observation was in complete contrast to some of the earlier studies which have shown high levels (OD >1.5) of anti-Acr IgM antibodies in ATB patients as well as healthy contacts [29,32,45,50]. Apart from the demographic differences in study populations, such discrepant results may also occur due to purely technical reasons.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We encountered a similar phenomenon in this study, which resulted in 'negative' (< 0) ΔOD values for anti-Acr IgM antibodies. This observation was in complete contrast to some of the earlier studies which have shown high levels (OD >1.5) of anti-Acr IgM antibodies in ATB patients as well as healthy contacts [29,32,45,50]. Apart from the demographic differences in study populations, such discrepant results may also occur due to purely technical reasons.…”
Section: Discussioncontrasting
confidence: 98%
“…Two of them have reported that IgA and IgG levels are higher in patients than in contacts or healthy subjects [29,30] and one study has reported that children with TB have higher IgG and IgM levels as compared to healthy children [31]. Another study has found that the level of anti-Acr IgM is significantly higher in LTBI than in active TB [32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the HspX protein, its increased representation in the 3955 strain compared to RUS_B0, which went down in the strain 2093, was observed. Previously, it was proposed that HspX can be used as a marker of the disease, including its latent form [21,22]. A reduced representation of this protein in the resistant strain casts doubts on its usefulness.…”
Section: Analysis Of Drug Resistance Genes On Multi-omics Levelmentioning
confidence: 99%
“…HspX is a Mycobacterium tuberculosis antigen (also known as α-crystallin) which is abundantly expressed under hypoxia 3,14 and in both active and latent forms of TB. 3,14,16 The utility of this antigen in the antibody-based diagnosis of pulmonary TB has already been established. [17][18][19] In another study, the detection of HspX messenger RNA was used to detect viable M. tuberculosis directly in sputum specimens from clinically suspected TB patients.…”
Section: Introductionmentioning
confidence: 99%